ANALISIS PERHITUNGAN BUNGA TABUNGAN UNTUK MENGHITUNG PPH FINAL PASAL 4 AYAT 2 YANG HARUS DIPOTONG PADA NASABAH BANK SULUTGO CABANG BITUNG - Kalangi, Felicia Maria; Elim, Inggriani; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
One of the objects of income tax article 4 paragraph 2 is the interest on savings. Every customer who saves in the bank will get interest on their savings and the interest will be taxed at a rate of 20% of the gross amount. The research objective was to find out the savings interest calculation and calculate the final income tax article 4 paragraph 2 that must be deducted at the Bank SulutGo customer in the Bitung branch and whether the final PPh deduction in Article 4 paragraph 2 was in accordance with the applicable tax regulations. The analytical method used is descriptive method, in the form of interviews and documentation. The results of the study show that Bank SulutGo Branch Bitung uses the daily balance method to calculate savings interest. Savings interest will be calculated automatically by the system and channeled directly to the customer's account. The tax rate imposed by Bank SulutGo in the Bitung Branch is in accordance with Law No. 36 of 2008 and PP No. 123 of 2015 which is 20% of the gross amount of interest.Keywords: Savings Interest Calculation, Final Income Tax Article 4 paragraph 2